Global aspects of marine pollution policy : the need for a new international convention. - Davis, W. Jackson (1990)
Discusses in overview the source and fate of marine pollutants. Suggests the establishment of a new international 'Convention for the Protection of the Oceans from Pollution', incorporating new waste management principles and having jurisdiction over all sources of marine pollution, including those from land-based sources.